Pola Komunikasi Guru Ngaji dalam Membina Akhlak Remaja Yayasan At-Tibyan di Kelurahan Mekarsari - Siti Aminah (Jurnal Riset Komunikasi Penyiaran Islam, 2021)
Abstract. The background of this research is the communication pattern of the Qur’an teacher in fostering adolescent morals based on the results of the study, namely using the triadic interpersonal communication pattern is quite efficient because it can target many mad'u and can see its development. However, seen from this study, it is also known that the morals of teenagers in the At-Tibyan foundation are still teenagers whose morals are not good. Because from a moral perspective, there are still some teenagers who do not obey the existing morals. Fostering youth morality is a mandatory thing that must be put forward by the AtTibyan Foundation, played by a Koran teacher as a preacher who conveys Islamic teachings. Thus, this thesis discusses the Communication Pattern of the Ngaji Teacher in fostering adolescent morality which is the basis of every education which is used as a foundation as a fortress from the influence of the times that cannot be separated from negative and misleading external culture. Thus, fostering adolescent morals has an important meaning and role in the formation of behavior for adolescents, because in fostering adolescent morals it is not only directed to the happiness of life in the world, but to happiness in the hereafter. This study uses a type of qualitative research method, using field studies (field research) in the data collection process. This study determines the subject and object of research by referring to the interview guidelines for conducting interviews, documentation, and observations. The results of this study indicate that the communication pattern of the Qur’an teacher which is carried out in fostering the morals of the At-Tibyan foundation youth in Mekarsari Village is a triadic Interpersonal Communication Pattern. This communication pattern is the right communication pattern to be used in the learning process and plays a very important role in making teenagers have good morals in the foundation environment and in their daily environment. Abstrak. Latar belakang penelitian ini pola komunikasi guru ngaji dalam membina akhlak remaja berdasarkan hasil penelitian yaitu menggunakan pola komunikasi Antarpribadi triadik sudah terbilang efisien sebab bisa menyasar terhadap banyak mad’u serta bisa melihat perkembangannya. Akan tetapi dilihat dari penelitian ini juga diketahui bahwa akhlak remaja di yayasan At-Tibyan masih terdapat remaja yang akhlaknya kurang baik. Karena melihat dari dari segi akhlakul karimahnya masih ada beberapa remaja yang tidak mentaati akhlak yang ada. Membina Akhlak remaja merupakan hal yang wajib yang harus dikedepankan oleh Yayasan AtTibyan yang diperankan oleh guru ngaji sebagai seorang da’i yang menyampaikan ajaran Islam. Demikian dengan skripsi ini yang membahas tentang Pola Komunikasi Guru Ngaji dalam membina Akhlak remaja yang merupakan dasar dari setiap pendidikan yang dijadikan pondasi sebagai benteng dari pengaruh perkembangan zaman yang tidak lepas dari budaya luar yang negatif dan cenderung menyesatkan. Dengan demikian maka membina akhlak remaja mempunyai arti dan peranan penting dalam pembentukan tingkah laku bagi remaja, sebab dalam membina akhlak remaja ini tidak hanya diarahkan kepada kebahagiaan hidup di dunia, akan tetapi untuk kebahagiaan di akhirat kelak. Penelitian ini menggunakan jenis metode penelitian kualitatif, dengan menggunakan study lapangan (field research) dalam proses pengumpulan datanya. Penelitian ini menentukan subjek dan objek penelitian dengan mengacu pada pedoman wawancara untuk melakukan wawancara, dokumentasi, dan observasi. iv Hasil dari penelitian ini menunjukan bahwa pola komunikasi guru ngaji yang dilakukan dalam membina akhlak remaja yayasan At-Tibyan di Kelurahan Mekarsari adalah Pola Komunikasi Antarpribadi triadik. Pola komunikasi ini adalah merupakan pola komunikasi yang tepat untuk digunakan dalam proses pembelajaran dan sangat berperan pentong dalam menjadikan remaja berakhlakul karimah dalam lingkungan yayasan maupun dilingkungan sehari-hari.